1979
DOI: 10.1016/0009-2614(79)80200-6
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Siegert eigenvalues for molecular systems: results for He(21,3S)+ H

Abstract: The variational calculation of Siegert eigenvalues has previously been shown to provide reliable positions and widths for atomic resonances. This approach is herein extended to molecular problems, and the first such calculations for a molecular autoionizing system, He(2 1 ,3S) + H ~ He + H+ + are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The atomic systems studied are H-He*͑2 3 S͒, 4 -9 -He*͑2 1 S͒, 4,7,8 He-He*(2 3 S,2 1 S), 10 He*͑2 3 S͒ -He*͑2 3 S͒, [11][12][13] -He*͑2 1 S͒, 12,13 Li-He*͑2 3 S͒, 9,14,15 -He*͑2 1 S͒, 14,15 Na-He*(2 3 S,2 1 S), 9,16 K-He*͑2 3 S͒, 17,18 and -He*͑2 1 S͒. 17 However, a few molecular systems are studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic systems studied are H-He*͑2 3 S͒, 4 -9 -He*͑2 1 S͒, 4,7,8 He-He*(2 3 S,2 1 S), 10 He*͑2 3 S͒ -He*͑2 3 S͒, [11][12][13] -He*͑2 1 S͒, 12,13 Li-He*͑2 3 S͒, 9,14,15 -He*͑2 1 S͒, 14,15 Na-He*(2 3 S,2 1 S), 9,16 K-He*͑2 3 S͒, 17,18 and -He*͑2 1 S͒. 17 However, a few molecular systems are studied.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,[19][20][21][22] This reason may be that calculations of resonance potentials ͑V*͒ and widths ͑⌫͒ are difficult. Hickman et al and Cohen et al obtained resonance potentials and widths for the H 2 -He*͑2 3 S͒, 6,19 -He*͑2 1 S͒ 8,19 systems, and performed dynamical calculations based on the potentials and widths obtained. 19, 23 Bentley 20 calculated the H 2 O-Ne* ͑2 3 P͒ potential, and explained the preference of the A 1 ionization.…”
Section: Introductionmentioning
confidence: 99%
“…These authors thus demonstrated that the SM could be employed in a more straightforward manner [with Im(k) < 0, throughout]. The purpose of this letter is to shed further light upon this situation by showing that the "tricks" [replacing Im(k) by -Im(k) or bya small positive number] used by Miller et al [2,3] are, in fact, valid because they can be viewed as nothing more than special coordinate rotation (CR) calculations involving L2 basis functions.…”
mentioning
confidence: 94%
“…6 is that one can scale a single orbital in any multi-electron Slater determinant; the antisymmetric nature of such determinants assures that indistinguishability is not violated. The physical motivation for considering this proposition is that only a single electron is unbound in the kind of electron-molecule scattering processes m a t commonly studied [2,3,4,6]; the remaining electrons are bound and should have their energy unchanged by coordinate rotation [ U I . …”
mentioning
confidence: 99%
See 1 more Smart Citation